Feeling and thought in collective action on social issues: Toward a systems perspective. Issue 7 (31st May 2021) - Bou Zeineddine, Fouad; Leach, Colin Wayne
Abstract: Theories of action have tended to view it—and its basis in thought and feeling—as static, discrete, mechanistic, and decontextualized. Moreover, studies of action have tended to be fragmented in academic silos. The consequences of these problems include a lack of cumulative and contextualized theory‐building, and an inability to recognize emergent, dynamic, and non‐linear causality, especially across levels of analysis. We argue that such problems could be partly alleviated with increased engagement with a meta‐theoretical perspective that has long been advocated for in psychology—the systems approach. In this view, thought, feeling, motivation, action, and context can be viewed as co‐evolving, inextricably linked, systems of systems. We illustrate the need for and benefit of this approach in the domain of collective action on social issues. We conclude that systems perspectives allow more contextualized, generalizable, conceptually rich, and applied directions for research in this domain.